Reconfigurable Memristive Pulse Generator Based on Pulse Shaping for Ultra Wideband Communication - Barraj, Imen; Neifar, Amel; Mestiri, Hassen; Masmoudi, Mohamed (Engineering, Technology & Applied Science Research, 2025)
This paper presents a novel reconfigurable memristive Pulse Generator (PG) designed for Ultra-Wideband (UWB) applications, leveraging the advanced pulse shaping techniques. The proposed design aims to improve the efficiency and flexibility of UWB communication systems, thereby contributing to the achievement of the "Sustainable Development Goal 9: Industry, Innovation, and Infrastructure" by promoting technological advances in the field of communications. The design utilizes the CMOS 0.18 µm technology operating at 1.8 V to achieve high performance and low power consumption. By employing constant resistance and dynamic resistance modulation, the proposed PG supports various modulation schemes, including Frequency-Shift Keying (FSK) and On-Off Keying (OOK), enhancing its adaptability and efficiency. The transmitter demonstrates significant energy efficiency with a low-duty cycle impulse approach, operating within the lower UWB band (3-5 GHz) to minimize interference. The simulation results indicate that the UWB generator achieves high data rates and improved spectral efficiency while maintaining compliance with the FCC regulations. This makes it ideal for integration into IoT devices, wearable technology, and other battery-powered applications. Therefore, the proposed design has the potential to enhance connectivity and data transmission capabilities, ultimately supporting the development of more efficient and reliable communication networks worldwide.